Pharmacotherapeutic considerations for the management of diabetes mellitus among hospitalized COVID-19 patients. (22nd January 2021) - Hasan, Syed Shahzad; Kow, Chia Siang; Bain, Amie; Kavanagh, Sallianne; Merchant, Hamid A.; Hadi, Muhammad Abdul
ABSTRACT: Introduction: Diabetes mellitus is one of the most prevalent comorbidities identified in patients with coronavirus disease 2019 (COVID-19). This article aims to discuss the pharmacotherapeutic considerations for the management of diabetes in hospitalized patients with COVID-19. Areas covered: We discussed various aspects of pharmacotherapeutic management in hospitalized patients with COVID-19: (i) susceptibility and severity of COVID-19 among individuals with diabetes, (ii) glycemic goals for hospitalized patients with COVID-19 and concurrent diabetes, (iii) pharmacological treatment considerations for hospitalized patients with COVID-19 and concurrent diabetes. Expert opinion: The glycemic goals in patients with COVID-19 and concurrent type 1 (T1DM) or type 2 diabetes (T2DM) are to avoid disruption of stable metabolic state, maintain optimal glycemic control, and prevent adverse glycemic events. Patients with T1DM require insulin therapy at all times to prevent ketosis. The management strategies for patients with T2DM include temporary discontinuation of certain oral antidiabetic agents and consideration for insulin therapy. Patients with T2DM who are relatively stable and able to eat regularly may continue with oral antidiabetic agents if glycemic control is satisfactory. Hyperglycemia may develop in patients with systemic corticosteroid treatment and should be managed upon accordingly.